Industrial cluster and knowledge creation: a bibliometric analysis and literature review - Raul Tarazona; Dayanis García-Hurtado; Carlos Devece; Valmir Emil Hoffmann (Multidisciplinary Journal for Education, Social and Technological Sciences)
The interaction between the development of industrial clusters and knowledge generation has become a fundamental element in driving innovation systems. Examining industrial clusters in knowledge creation terms is interesting for policymakers, investors, businesses and academia. This article provides a thematic and intellectual overview of the existing scientific literature on industrial clusters, their evolution and their relation with knowledge creation. The aim is to identify the scientific literature foundations in this area, different intellectual, conceptual and social structures, and trends in the research field. The study is a bibliometric analysis, whose results show that researchers’ topics of interest have considerably evolved over the last four decades. Initially, most studies focus on policies for efficient clusters management and later, starting in the 2010s, they evolve towards the importance of the networks of resources and knowledge that clusters provide, and how to promote learning and innovation as a key activity for economic development.